Design and Implementation of Electronic Queue System at Walenrang Health Center for Service Optimization - Rizky Amalia Sugiman; Dianradika Prasti; Suparman Suparman (Brilliance: Research of Artificial Intelligence, 2025)
This study aims to design, develop, and implement an Android-based electronic queuing system to enhance the effectiveness, efficiency, and overall quality of healthcare services at Walenrang Community Health Center. The manual queuing system previously applied often caused patient congestion, long waiting times, service delays, and discomfort for both patients and staff. To overcome these problems, an electronic queuing system was created, allowing patients to take queue numbers online, monitor the real-time status of the queue, access detailed service information, and view their visit history conveniently. This system was developed using a Research and Development (R&D) approach, following the waterfall model as the software development method. Evaluation of the system involved three expert validators, resulting in a validation score of 95.17%, which classifies the system as highly feasible for implementation. Furthermore, usability testing with 12 user respondents revealed an average satisfaction score of 94 out of 100, indicating a very high level of user satisfaction regarding ease of use, speed of access, and accuracy of queue information. Based on these results, the implemented system has proven effective in improving the efficiency of healthcare service delivery while providing greater convenience, comfort, and accessibility for the community, thereby supporting a more organized and patient-friendly healthcare environment.